Prognostic nutritional index is a predictor of mortality in elderly patients with chronic kidney disease - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER, 2022)
Purpose Prognostic nutritional index (PNI), a composite indicator of inflammation and nutritional status, has recently been recognized as an independent prognostic marker for chronic kidney disease (CKD). We aimed to investigate PNI and its relationship with mortality in elderly patients with CKD. Methods Three hundred and fifty-nine patients over the age of 80 years with stage 3-4 CKD were enrolled in this retrospective study. PNI was used to assess the nutritional status of the patients. Patients were divided into two different groups as deceased and survived and as low PNI (< 39) and high PNI (>= 39) according to median value of PNI. Results The mean age of the patients was 85.7 +/- 3.7 years. One hundred and ninety-five (54.3%) patients died during follow-up. Multivariate analysis revealed that male gender, PNI, proteinuria, and diabetes mellitus (DM) were independent predictors of mortality in elderly patients with CKD. When patients with low PNI were compared to those with high PNI, initiation of dialysis and mortality rate were significantly higher whereas albumin, hemoglobin and lymphocyte count were lower. Pearson correlation analysis showed that PNI was significantly correlated with albumin (r = 1.000, p < 0.001), hemoglobin (r = 0.340, p < 0.001) and eGFR (r = 0.123, p = 0.020). Hemoglobin was an independent predictor of PNI in multivariate analysis. Conclusion In this study, we observed that PNI was significantly associated with mortality over the age of 80 years in patients with CKD and can be used to monitor nutritional status in this patient population.
Keywords: Chronic kidney disease; Elderly patients; Mortality; Prognostic nutritional index; TYPE-2 DIABETES-MELLITUS; PERITONEAL-DIALYSIS; RISK-FACTOR; MALNUTRITION; ASSOCIATION; PREVALENCE; FAILURE; INFLAMMATION; OUTCOMES